Paul Laurence Dunbar : portrait of a poet - Reef, Catherine (Berkeley Heights, NJ : Enslow Publishers, 2000)
A biography of the poet who faced racism and devoted himself to depicting the black experience in America
"Works by Paul Laurence Dunbar": p. 113-114
Includes bibliographical references (p. 124) and index
Keywords: Dunbar, Paul Laurence, -- 1872-1906 -- Juvenile literature; Poets, American -- 19th century -- Biography -- Juvenile literature; African American poets -- Biography -- Juvenile literature; African Americans in literature -- Juvenile literature